Delayed seropositivity is associated with lower levels of SARS-CoV-2 antibody levels in patients with mild to moderate COVID-19 - Marwa M. Fekry; Hanan Soliman; Mona H. Hashish; Heba S. Selim; Nermin A. Osman; Eman A. Omran (SpringerOpen, 2023)
Abstract Background Patients with COVID-19 can develop a range of immune responses, including variations in the onset and magnitude of antibody formation. The aim of this study was to investigate whether SARS-CoV-2 antibody levels vary in patients with mild to moderate COVID-19 in relation to the onset (days) of their post-symptom seropositivity and to explore host factors that may affect antibody production Methods This was a prospective, multiple measurements study involving 92 PCR-confirmed patients with mild to moderate COVID-19. Antibody testing for anti-nucleocapsid (anti-NP) and spike proteins (anti-S) was performed using ELISA tests. Serum samples were collected over a period of 55 days from symptom onset of COVID-19 infection, and repeated as necessary until they turned positive. Results No significant differences were found between the positivity rates of anti-S or anti-NP regarding any clinical symptom (p > 0.05). The majority of patients who tested positive for anti-NP and anti-S showed early seropositivity (within 15 days of symptom onset) (75.9% for anti-NP and 82.6% for anti-S). Younger patients, those without chronic diseases, and non-healthcare workers had the highest percentage of seroconversion after day 35 post-symptom onset (p = 0.002, 0.028, and 0.036, respectively), while older patients and those with chronic diseases had earlier seropositivity and higher anti-NP levels (p = 0.003 and 0.06, respectively). Significantly higher anti-S ratios were found among older (p = 0.004), male (p = 0.015), and anemic patients (p = 0.02). A significant correlation was found between both antibodies (p = 0.001). At the end of the study, the cumulative seroconversion rate for both antibodies was almost 99%. Conclusions Some COVID-19 patients may exhibit delayed and weak immune responses, while elderly, anemic patients and those with chronic diseases may show earlier and higher antibody responses.